Histoid leprosy - A rare clinical presentation, - Angélica Bauer; Letícia Maria Eidt; Renan Rangel Bonamigo; Renata Heck (Sociedade Brasileira de Dermatologia, 2021)
Abstract Histoid leprosy is considered a rare form of lepromatous leprosy. Its peculiar clinical picture makes its diagnosis a challenging one, which can delay starting treatment and perpetuate the disease as endemic. In addition to representing a reservoir of bacilli, and being an important means of contamination, these patients have greater resistance to standard treatment. This is a report of a typical case of this rare presentation, aiming to share the knowledge and favor earlier diagnosis of the disease.